Structure and Mechanical Properties of Hafnium Doped with Yttrium Oxide - S.V. Chornobuk; M.I. Cherednyk; O.Yu. Popov (Журнал нано- та електронної фізики)
The influence of Y2O3 nanoparticles on structure and mechanical properties of hafnium is investigated. Scanning electron microscopy and energy dispersive analysis showed that yttria nanoparticles melt in vacuum arc forming interstitial solution Hf (Y, O). Samples structure investigation showed the growth of internal microstresses which causes material cracking with Y2O3 concentration higher than 0.3 wt. %. Hafnium microhardness is shown to be increasing with yttria content.